Diagnostic accuracy of axillary staging by ultrasound in early breast cancer patients. Issue 135 (February 2021) - Riedel, Fabian; Schaefgen, Benedikt; Sinn, Hans-Peter; Feisst, Manuel; Hennigs, André; Hug, Sarah; Binnig, Angela; Gomez, Christina; Harcos, Aba; Stieber, Anne; Kauczor, Hans-Ulrich; Sohn, Christof; et al.
Abstract: Background: Axillary ultrasound (AUS) is a standard procedure in the preoperative clinical identification of axillary metastatic lymph node (LN) involvement. It guides decisions about local and systemic therapy for patients with early breast cancer (EBC). But there is only weak evidence on the diagnostic criteria and standard interpretation. The aim of this study was to assess the performance of AUS in the detection and exclusion of LN metastases. Methods: In a retrospective single-center study, 611 consecutive EBC patients with 622 axillae underwent AUS +/- core needle biopsy (CNB) plus axillary surgery, i.e. sentinel lymph node biopsy and/or axillary lymph node dissection. For all patients, AUS image documentation of at least the most suspicious LN was saved during the initial diagnostic work-up. The diagnostic outcome measures were sensitivity, specificity, accuracy, Youden-index (YI), and diagnostic odds ratio (DOR) on the basis of the daily routine interpretation and on the basis of previously recommended diagnostic criteria by two blinded examiners. Results: On the basis of the daily routine interpretation, AUS had a sensitivity (95 % CI) of 53.3 % (46.4–60.1), a specificity (95 % CI) of 93.6 % (90.8–95.8), an accuracy (95 % CI) of 79.7 % (76.4–82.8), a YI (95 % CI) of 0.47 (0.40 – 0.54), and a DOR (95 % CI) of 16.75 (10.37–27.05). Systematic application of previously recommended diagnostic criteria did not improve the diagnostic accuracy of routinely interpreted AUS. Conclusion: AUS performance alone is not sufficient to accurately identify or exclude axillary metastatic disease in unselected patients with EBC.